Método fundamentado em processamento digital de imagens para contagem automática de unidades formadoras de colônias - Alves, Gabriel Marcelino (2006)
This work presents a computer aided system for automated counting of colony formation units in Petri dishes. The method implemented uses digital image processing, and among them Hough transform for circular objects and Match for correlation with objects having different forms. The method was developed based on the visual Borland Builderr C++ environment, and for the image acquisition a luminance equalization system was used to allow stabilized and continuous 1,200 lux. For the validation of the method, samples containing Acidithiobacillus ferrooxidans, Escherichia Coli, and Staphylococcus aureus were analyzed. Results have shown the potentiality of the methodology, which is applied for laboratory applications that involved the quantification of bacterial colonies in a solid culture environment.